Associations of ischemic heart disease with brain glymphatic MRI indices and risk of Alzheimer's disease - Wang, Ming-Liang; Yu, Meng-Meng; Sun, Zheng; Zhang, Jun-Jie; Zhang, Jing-Kun; Wu, Xue; Wei, Xiao-Er; Li, Yue-Hua (Journal of Prevention of Alzheimer's Disease, The, 2025)
The impact of ischemic heart disease (IHD) on the brain glymphatic MRI indices and risk of Alzheimer's disease (AD) remains largely unclear. This study aimed to investigate the associations between IHD, brain glymphatic MRI indices and risk of AD. A total of 1385 non-dementia subjects (55.2 % male, mean age 73.53) were included. Diffusivity along the perivascular space (DTI-ALPS), free water (FW) and choroid plexus volume were used to reflect glymphatic function. The associations of IHD with MRI derived glymphatic indices, PET amyloid, tau and cognitive performance were explored by multiple regression analysis. IHD were tested as predictors of clinical progression using cox proportional hazards modeling. The mediation effect of MRI derived glymphatic indices on the relationship between IHD and cognitive changes was investigated. Individuals with IHD exhibited glymphatic dysfunction revealed by lower DTI-ALPS (p = 0.035), higher FW (p < 0.001), and higher choroid plexus volume (p = 0.019). IHD had poorer cognitive performance in MMSE (p = 0.022), ADNI-MEM (p = 0.001) and ADNI-MF (p = 0.006), and more amyloid deposition (p = 0.007). IHD had a higher diagnostic conversion risk (HR = 1.321, 95 % CI = 1.003–1.741). IHD was associated with longitudinal cognitive decline in all cognitive tests (p < 0.05 for all) and FW (β = 0.012, 95 % CI 0.001, 0.023, p = 0.038). FW demonstrated an indirect effect (β = -0.0009, 95 % CI: -0.0034, -0.0001) and mediated 13.85 % effect for the relationship between IHD and ADNI-EF decline. IHD is independently associated with AD risk, and brain glymphatic dysfunction may partially mediate this relationship.